The Firre locus produces a trans-acting RNA molecule that functions in hematopoiesis - Jordan P. Lewandowski (Nature Portfolio, 2019)
LncRNA loci potentially contain multiple modes that can exert function, including DNA regulatory elements. Here, the authors generated genetic models in mice to dissect the role of the syntenically conserved lncRNA Firre in the context of hematopoiesis.